Canopy1, a positive feedback regulator of FGF signaling, controls progenitor cell clustering during Kupffer's vesicle organogenesis - Takaaki Matsui (2018)
The assembly of progenitor cells is a crucial step for organ formation during vertebrate development. Kupffer's vesicle (KV), a key organ required for the left-right asymmetric body plan in zebrafish, is generated from a cluster of ∼20 dorsal forerunner cells (DFCs). Although several genes are known to be involved in KV formation, how DFC clustering is regulated and how cluster formation then contributes to KV formation remain unclear. Here we show that positive feedback regulation of FGF signaling by Canopy1 (Cnpy1) controls DFC clustering. Cnpy1 positively regulates FGF signals within DFCs, which in turn promote Cadherin1-mediated cell adhesion between adjacent DFCs to sustain cell cluster formation. When this FGF positive feedback loop is disrupted, the DFC cluster fails to form, eventually leading to KV malformation and defects in the establishment of laterality. Our results therefore uncover both a previously unidentified role of FGF signaling during vertebrate organogenesis and a regulatory mechanism underlying cell cluster formation, which is an indispensable step for formation of a functional KV and establishment of the left-right asymmetric body plan.